2015
DOI: 10.3168/jds.2015-9393
|View full text |Cite
|
Sign up to set email alerts
|

The influence of age and weaning on permeability of the gastrointestinal tract in Holstein bull calves

Abstract: Fourteen Holstein bull calves were used in a randomized complete block design to investigate the effect of calf age and weaning on permeability of the gastrointestinal tract (GIT). Calves were randomly assigned to 1 of 2 treatments: (1) a weaning protocol that was initiated on d 35; WN; n=7), or (2) a control treatment where calves were not weaned (CON; n=7). Calves were bottle-fed milk replacer (150 g/L), in 3 equal portions/d targeting 15% of their body weight (BW) in liquid milk intake [approximately 21.1g/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 33 publications
2
54
0
2
Order By: Relevance
“…In that experiment, the high-grain challenge decreased the expression of tight junction and increased the apoptotic cell numbers in both tissues. These results align with hypotheses related to dietary transition of the lower gut of the calf during weaning (Wood et al, 2015), in which permeability of the gut was shown to increase during weaning (provision of rapidly fermentable concentrates). Based on the structure, the multilayered ruminal SSE may be less permeable to allow the transmigration of endotoxins and bacteria compared with the single layer of the CE in the lower gut (Figure 1; Metzler-Zebeli et al, 2013) and, based on permeability measurements, the duodenum may be a region with particularly high paracellular permeability (Penner et al, 2014).…”
Section: Transition To Highly Fermentable Dietssupporting
confidence: 89%
See 1 more Smart Citation
“…In that experiment, the high-grain challenge decreased the expression of tight junction and increased the apoptotic cell numbers in both tissues. These results align with hypotheses related to dietary transition of the lower gut of the calf during weaning (Wood et al, 2015), in which permeability of the gut was shown to increase during weaning (provision of rapidly fermentable concentrates). Based on the structure, the multilayered ruminal SSE may be less permeable to allow the transmigration of endotoxins and bacteria compared with the single layer of the CE in the lower gut (Figure 1; Metzler-Zebeli et al, 2013) and, based on permeability measurements, the duodenum may be a region with particularly high paracellular permeability (Penner et al, 2014).…”
Section: Transition To Highly Fermentable Dietssupporting
confidence: 89%
“…More recently, Wood et al (2015) demonstrated that gastrointestinal permeability decreases (suggesting improved barrier function) as calves age from 17 to 42 d. However, the authors noted that weaning alters this age-dependent process. Wood et al (2015) characterized regional responses for permeability and innate immune responses and demonstrated that the rumen, duodenum, and jejunum are regions at the greatest risk of impaired barrier function. This differs from Malmuthuge et al (2013), where the jejunum, ileum, and cecum were implicated as regions with reduced barrier function based on mRNA abundance of claudin 4.…”
Section: Weaningmentioning
confidence: 99%
“…Rumen development is considered incomplete before 8 wk of age (Meale et al, 2017). More gradual (Meale et al, 2015) or delayed weaning (Eckert et al, 2015;Wood et al, 2015) could allow more time for rumen development and reduce the contrasts among treatments. On the other hand, calves on the 80:20 or 70:30 treatments did not consume more ME than 90:10 calves, and thus it seems that in these cases feed intake was limited by total energy supply from solid feed.…”
Section: Resultsmentioning
confidence: 99%
“…Intestinal barrier function and intestinal permeability (IP) play an important role in health, and alteration of the gut barrier seems to have multiple consequences facilitating the onset of a variety of diseases (Bischoff et al, 2014). In animal production systems, gastrointestinal tract barrier function is known to be compromised during diarrhea (Klein et al, 2008), weaning (Moeser et al, 2007;Wood et al, 2015), heat stress Pearce et al, 2013), and rumen acidosis (Khafipour et al, 2009;Minuti et al, 2014). The direct consequence of intestinal barrier dysfunction is the increased leakage of luminal antigens into the bloodstream, with the potential to initiate an inflammatory response (Kvidera et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Lactulose-d-mannitol and Cr-EDTA permeability tests have been validated to assess gut integrity in humans (Andre et al, 1987;Jalonen, 1991) and in other species, including dogs (Hall and Batt, 1991;Quigg et al, 1993), rats (Turner et al, 1988), and calves (Klein et al, 2007(Klein et al, , 2008Araujo et al, 2015;Wood et al, 2015). A permeability test is a noninvasive diagnostic tool that provides information on the integrity of the mucosa and on its protective barrier function and may help to predict responses of the intestines to many potentially harmful stimuli (e.g., physiological, pharmaceutical, and nutritional; Klein et al, 2007).…”
Section: Introductionmentioning
confidence: 99%